(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Carboniferous oil and gas fields have been found in different areas in the eastern part of the Junggar Basin on a large scale, indicating that the Carboniferous rocks of the Junggar Basin have a huge potential for oil and gas exploration. The Batamayineishan Formation in the eastern part of the Junggar Basin, which contains volcanic rocks and pyroclastic rocks, has been studied to investigate the reservoir characteristics and identify the formation mechanism of the rocks of this formation. Secondary pores and fractures dominate the reservoir space in the volcanic rocks of the Batamayineishan Formation. Using the methods of petrography, pressure-controlled mercury injection (PMI), and electron probe microanalysis (EPMA), the reservoir characteristics and diagenetic history of the volcanic rocks of the Batamayineishan Formation in the Shuangjingzi area were studied. A theoretical framework is established to provide favorable guidance for exploring Carboniferous volcanic rocks in the Junggar Basin. The results of mercury injection indicate that the average pore throat radius and porosity of the volcanic rocks are 0.068 µm and 6.62%, respectively. Permeability remains stable and does not show a significant change with an increase in porosity. Despite the high porosity, the permeability is relatively low, reflecting isolated and non-connected primary pores. The average value of permeability is relatively low (0.424×10-3 µm2), which typically suggests narrow micro-throats. Primary gas pores fill and develop amygdales on a large scale. In addition, the dissolution pores developed by dissolution and alteration also compensated for the decrease in the original gas pore volume.